Association of immature platelets with perioperative complications in neurosurgery. (31st December 2023) - Anetsberger, Aida; Bernlochner, Isabell; Jungwirth, Bettina; Blobner, Manfred; Meyer, Bernhard; Kochs, Eberhard F; Bongiovanni, Dario; Schmid, Sebastian; Langgartner, Clemens; Baumgart, Lea; Gempt, Jens
Abstract: Immature platelets are newly formed platelets with an increased prothrombotic potential. This study evaluates whether immature platelets are associated with relevant complications in neurosurgical patients. Data were obtained in the frame of a prospectively conducted observational study exploring the association between immature platelets and major cardiovascular events after surgery. Immature platelet fraction (IPF) and H-IPF (highly fluorescent immature platelet fraction) were measured preoperatively and postoperatively at the neurosurgical ward (24–72 hours after surgery). Therapy-relevant complications after surgery were stratified using the Clavien-Dindo Grade (CDG >2) as primary outcome. Data were analyzed in 391 neurosurgical patients. While preoperatively there were no differences in IPF or H-IPF, patients with higher therapy-complication grades had higher values post-op compared to patients with lower grade complications (≤2 CDG). Cut-off values identified by receiver operating characteristic curve analysis revealed that there were significantly more patients with H-IPF ≥0.95% in the group with serious complications (CDG >2) [odds ratio OR (95% confidence interval CI) = 2.06 (1.09–3.9), p = .025], whereas this association was not present for the IPF cutoff value. In a multivariate model, H-IPF≥0.95% was independently associated with serious complications after surgery [OR (95% CI) = 1.97 (1.03–3.78), p = .041]. These findings suggest that H-IPF is associated with surgical complications and may improve risk stratification of neurosurgical patients (clinicaltrials.gov: NCT02097602, registration date: 27/03/2014). Plain Language Summary: What is the context? Immature platelets are newly formed platelets with a higher thrombotic potential and play an important role in atherothrombotic events. Higher levels of immature platelets were observed in patients with acute coronary syndrome or stroke. Lately, the focus in immature platelet research shifted from observation to outcomes. Immature platelets were identified as independent predictors of major cardiovascular events in cardiologic patients with coronary artery disease. Besides, an association between immature platelets and major cardiovascular events was described in surgical patients after non-cardiac surgery. What is new? This study builds on these findings and extends the focus to perioperative complications after neurosurgery. The data were obtained prospectively in the frame of an observational clinical trial exploring the association of immature platelets and major cardiovascular events in general. Data measured in the neurosurgical cohort of that study (391 neurosurgical patients) were analyzed in the present work. Within the limitations of our study, our analyses suggest that the postoperative IPF (immature platelet fraction) and H-IPF (highly fluorescent immature platelet fraction) values, which were measured at the neurosurgical ward after surgery are both associated with higher therapy-relevant complication grades (>2 according to Clavien-Dindo Grade), whereas preoperatively obtained values were not. What is the impact? This is the first study showing a relationship between immature platelets and therapy-relevant perioperative complications in neurosurgical patients. It could be a pilot trial for varied scientific questions including risk stratification of neurosurgical patients.